NONLINEAR CONTROL OF UNMANNED SURFACE VEHICLE - Hasan, Hasnawiya (Jurnal Riset Teknologi Kelautan, 2016)
An Unmmaned Surface Vehicle is a marine vehicle which has a complicated nonlinear model and partially uncertain parameters in its model. Therefore, an USV needs an advance control technique to solve this complicated problem.Â Nonlinear control is the most suitable technique to control this model. Nonlinear control is less sensitive to parameter uncertainty and disturbance perturbation which is beneficial for Unmanned Surface Vehicle which has highly disturbance parameter perturbation also. In the previous work, a disturbance model has never been considered in the control process due to highly perturbation in the model. Therefore, this work take account of the disturbance factors of Unmanned Surface Vehicle model.